2021
DOI: 10.7759/cureus.18151
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Granuloma Annulare With Pentoxifylline and Oral Vitamin E: A Case Series

Abstract: Granuloma annulare (GA) is a difficult-to-treat granulomatous skin disorder characterized by multiple annular, raised, and erythematous lesions. While numerous therapies have been proposed, there is currently no clear gold standard of treatment.We present a series of five patients with biopsy-proven generalized GA who were treated with pentoxifylline and oral vitamin E. Each patient in this series had at least a one-year history of GA refractory to other treatments. After three months of treatment, four of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Some of these less commonly utilized treatments for GA include vitamin E and pentoxifylline. 2 Vitamin E, or tocopherol, has been used for treating GA since the 1940s. 3 Many patients view alternative treatments favorably, and this is particularly relevant in patients who have failed to respond to conventional therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these less commonly utilized treatments for GA include vitamin E and pentoxifylline. 2 Vitamin E, or tocopherol, has been used for treating GA since the 1940s. 3 Many patients view alternative treatments favorably, and this is particularly relevant in patients who have failed to respond to conventional therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Topical formulations oxidize quickly when exposed to light and air. Additional considerations include interactions with vitamin K–dependent clotting factors in patients taking large doses of 1000 IU of oral vitamin E. 2 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…Granuloma annulare (GA) is a cutaneous granulomatous inflammatory disease characterized by annulare erythematous papules and plaques 27 . Four case reports and one retrospective review were identified, totaling 37 patients treated with pentoxifylline for GA 27–31 .…”
Section: Granulomatousmentioning
confidence: 99%
“…Granuloma annulare (GA) is a cutaneous granulomatous inflammatory disease characterized by annulare erythematous papules and plaques. 27 Four case reports and one retrospective review were identified, totaling 37 patients treated with pentoxifylline for GA. [27][28][29][30][31] A retrospective review of 27 patients treated with pentoxifylline reported improvement in 56% and complete resolution occurred in 15% patients. 31 Five additional cases treated with pentoxifylline all had drastic improvement of lesions within 6 months.…”
Section: Granuloma Annularementioning
confidence: 99%
“… 1 , 2 Although hydroxychloroquine, dapsone, methotrexate, and phototherapy have the most evidence in GGA, data regarding other systemic medications, such as colchicine, pentoxifylline, and minocycline, are generally limited to case reports and small case series (<10 patients). 2 , 3 , 4 , 5 We evaluated our experiences with colchicine, pentoxifylline, and minocycline in 42 patients with GGA.…”
mentioning
confidence: 99%